Technical Study of Automated High-Throughput High-Sensitive Ceruloplasmin Assay on Dried Blood Spots-Reinstate the Potential Use for Newborn Screening of Wilson Disease - Chloe Miu Mak; Ching Tung Choi; Tsz Ki Wong; Hanson Heearn Chin; Hillman Kai Yin Lai; Koon Yu Yuet (MDPI AG, 2022)
In this study, we modified a fully automatic immunoassay on ceruloplasmin concentration on dried blood spots (DBS) to increase its analytical sensitivity in order to accurately differentiate newborns from true Wilson disease (WD) patients. Modifications to the assay parameters of the Roche/Hitachi Cobas c systems immunoturbidimetric assay are adjusted to lower the limit of quantitation to 0.60 mg/L from 30 mg/L. This enables sensitive measurement of ceruloplasmin in eluent after DBS extraction. In addition, reference intervals and receiver operating characteristic curve analysis for diagnostic cut-off were established using DBS of neonates and WD adult patients. After DBS whole blood calibration, the 95th percentile of the reference interval for newborns was 86-229 mg/L. The cut-off value of 54 mg/L was found to be the most optimal point for differentiating true adult WD from newborn controls. This test shows a high area under curve of 1.000 with 100% sensitivity and specificity in differentiating normal newborns from WD adult samples. However, the results should be further validated with true newborn WD patient samples together with the consideration of other factors that can also lead to low ceruloplasmin levels. This test shows application potential in newborn screening for WD, which can save lives through early identification and timely treatment.